2016
DOI: 10.1177/0009922816645516
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Perceptions of Cell Phone–Based, Health-Related Communication With Adolescents in an Economically Depressed Area

Abstract: We examined the feasibility and perception of cell-based (texting, voicemail [VM], and email/social media), health-related communication with adolescents in Genesee County, MI, where 22% reside below the poverty level. Results of an anonymous survey found that 86% of respondents owned a cell phone, 87% had data, 96% texted, 90.5% emailed/used social media, and 68% had VM. Most adolescents were interested in cell-based communication via texting (52%), VM (37%), and email/social media (31%). Interest in types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This finding parallels studies that suggest that the use of mobile technology for communication (eg, text messaging) is preferred over email as a means of communication among many patients. 23 This suggests that use of mobile technology might be a similarly preferred method for health education over current strategies. Additionally, the decrease in email ownership and utilization among patients over time emphasizes the ever-changing nature of technological preferences.…”
Section: Discussionmentioning
confidence: 99%
“…This finding parallels studies that suggest that the use of mobile technology for communication (eg, text messaging) is preferred over email as a means of communication among many patients. 23 This suggests that use of mobile technology might be a similarly preferred method for health education over current strategies. Additionally, the decrease in email ownership and utilization among patients over time emphasizes the ever-changing nature of technological preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Research to date shows some promising results. For example, a study that examined the feasibility of using cell-based communication with young people in an economically depressed area found that the majority of participants had cell phones, sent text messages and used other technology features (Sawni et al, 2016). Additionally, many were open to receiving health-related messages via mobile.…”
Section: Discussionmentioning
confidence: 99%
“…Sawni et al looked at communicating with adolescents in the USA in an area with a high level of poverty. They found that using cell phones was a very promising way to effectively communicate with that population through texting, phone calls/voicemail, email, and social media [ 22 ].…”
Section: Discussionmentioning
confidence: 99%